KOMUNIKASI INTERPERSONAL PASANGAN TA’ARUF ONLINE DATING DI RUMAHTAARUF.COM - Mardianti, Permata (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2019)
The emergence of the new media of the internet has shifted the definition of interpersonal communication. Furthermore, the emergence of social networks disclose new chance for agencies that offer dating through an online service or commonly known as online dating. One of them is Rumahtaaruf.com. This research focuses on how the motive in choosing the couples through Rumahtaaruf.com and how the interpersonal communication between the couple. This research uses qualitative method with phenomenological approach. The data obtained through interviews and literature studies, while informants in this study are couples who have married after meeting through Rumahtaaruf.com. The results show that the reason for choosing a partner based on because of motive, present motive and in order to motive. The because of motive evokes a criteria in selecting a partner such as education, age, occupation, physical attractiveness, the family response, and culture.Whereas the motive of the present are the development of interpersonal communication and the enhancement of interpersonal relationship between the couple which strengthened after the wedding.The motive of the present relates to the in order to motive of partner, for examples household life and economic conditions. To cite this article (7th APA style):Mardianti, P., Supratman, L. P. & Rina, N. (2019). Komunikasi Interpersonal Pasangan Ta’aruf Online Dating di Rumahtaaruf.Com [Interpersonal Communication of the Ta’aruf Online Dating Couple]. Journal Communication Spectrum, 9(1), 57-66. http://dx.doi.org/10.36782/jcs.v9i1.1585